2015
DOI: 10.1159/000381327
|View full text |Cite
|
Sign up to set email alerts
|

Can Rituximab Improve the Outcome of Patients with Nodular Lymphocyte-Predominant Hodgkin's Lymphoma?

Abstract: Background: Nodular lymphocyte-predominant Hodgkin's lymphoma (NLPHL) is a rare subtype of Hodgkin's lymphoma showing strong CD20 expression. The role of rituximab in treating NLPHL still needs clarification. Methods: We retrospectively reviewed the outcome of 23 patients with NLPHL treated with rituximab alone or in combination with chemotherapy and/or radiotherapy as part of their first- or second-line treatment. Results: The median follow-up of the whole group was 67 months, and all patients remained alive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Rituximab combined with CHOP chemotherapy was an effective treatment approach in adult patients with advanced stage nLPHL (Fanale et al , ). A few other studies have similarly shown a clear therapeutic benefit of combining rituximab with chemotherapy in patients with refractory or relapsed nLPHL (Advani et al , ; Lazarovici et al , ; Mocikova et al , ; Shankar et al , ). The relapse rate in the chemotherapy only group in our cohort compared to the rituximab plus chemotherapy group was nearly double (15%; 3/20 vs. 8·3%; 1/12).…”
Section: Discussionmentioning
confidence: 92%
“…Rituximab combined with CHOP chemotherapy was an effective treatment approach in adult patients with advanced stage nLPHL (Fanale et al , ). A few other studies have similarly shown a clear therapeutic benefit of combining rituximab with chemotherapy in patients with refractory or relapsed nLPHL (Advani et al , ; Lazarovici et al , ; Mocikova et al , ; Shankar et al , ). The relapse rate in the chemotherapy only group in our cohort compared to the rituximab plus chemotherapy group was nearly double (15%; 3/20 vs. 8·3%; 1/12).…”
Section: Discussionmentioning
confidence: 92%
“…However, the advantage offered by the introduction of rituximab in association with chemotherapy is currently still under debate. 8 , 10 , 15 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role of rituximab combined with chemotherapy, feasibility and efficacy of this approach has been previously described. Fanale et al 13 reported an excellent outcome in 27 patients with NLPHL treated with R-CHOP (5-year PFS 88.5% and 5-year OS of 100%) and Mocikova et al 15 reported a 5-year PFS of 90% and a 5-year OS of 100% in 23 patients treated with immunochemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No transformation into aggressive lymphoma was observed [7]. In this issue of Acta Haematologica , a retrospective analysis by Mocikova et al [8] reports the outcome of 23 patients with newly diagnosed (n = 13) or relapsed (n = 10) NLPHL who had rituximab-containing therapy. The treatment consisted of single-agent rituximab (n = 12), rituximab plus radiotherapy (n = 2), rituximab plus chemotherapy with CHOP, ABVD (Adriamycin, bleomycin, vinblastine, dacarbazine), BEACOPP (bleomycin, etoposide, Adriamycin, cyclophosphamide, vincristine, procarbazine, prednisone) or DHAP (dexamethasone, high-dose cytarabine, cisplatin; n = 11), and rituximab plus chemotherapy (ABVD or BEACOPP) plus radiotherapy (n = 4), respectively.…”
mentioning
confidence: 99%